Dynamic behaviour of adobe bricks in compression: The role of fibres and water content at various loading rates. (10th January 2020) - Li Piani, T.; Weerheijm, J.; Peroni, M.; Koene, L.; Krabbenborg, D.; Solomos, G.; Sluys, L.J.
Highlights: Comprehensive characterization of adobe material at a wide range of strain rates. Quali-quantitative role of interstitial water in adobe in statics and dynamics. Quali-quantitative role of mixing fibers in adobe in statics and dynamics. Constitutive modelling of adobe including DIF functions in dynamics. Abstract: This paper presents the results of an experimental research aimed at assessing the material performance of adobe bricks in compression for a wide range of induced strain rates, from statics to high velocity impact. Adobe connotes a traditional masonry whose bricks are made of sundried soil mixtures possibly reinforced with natural fibres and joined together using mud mortar. The inclusion of fibre and the presence of water in the mixture have a dominant effect on the mechanical performance of adobe bricks and masonry. Their influence on the dynamic behaviour of this material is quantified and interpreted in this study at high strain rates also with data produced through Hopkinson bar testing. Appropriate dynamic increase factors and constitutive equations for adobe materials in dynamics are also investigated. The paper presents the experimental campaign, shows the main results and offers qualitative and quantitative interpretations for the principal damage patterns observed.